Yield strength and hardness of micron-sized powders measured in the diamond cell. Issue 4 (2nd October 2021) - Chudinovskikh, L.; Boehler, R.
ABSTRACT: When powders of polycrystalline transparent materials are compressed in the diamond cell, they undergo a change from translucent to transparent. This effect is due to plastic deformation of the grains leading to a reduction in the size of voids responsible for light scattering. The pressures of the onset and saturation of the optical transmission corelate respectively well with the previously reported yield strengths and hardness obtained by different techniques. From ten measurements on MgO, SiO2, Al2O3, olivine, pyroxene, garnet and a perovskite, we find a ratio between hardness and yield strength of three, which is generally accepted. Preliminary high temperature measurements with the double-sided laser heating technique show that this method may be used for determining rheological properties of minerals at P-T conditions of the deep Earth. This technique for obtaining high optical transmission in polycrystalline materials may also be of interest for modern solid state laser materials.